Upaya Menggalakkan Tanaman Toga Dalam Upaya Pemenuhan Gizi Ibu Nifas - Nur Mufidah Alfi (CV. Multi Kreasi Media, 2025)
Public health is an important aspect of a country’s development. Efforts to improve the quality of life of the community through health programs are one of the main priorities in various national policies. Family Medicinal Plants (TOGA) are home-cultivated plants that have medicinal properties. Increasing public awareness, motivation, and capacity to live a healthy life will accelerate the achievement of optimal health status. Therefore, enhancing community capacity for independent health care through the utilization of TOGA serves as a form of first aid for individuals and families. The existence of TOGA functions not only as a source of traditional medicine but also as an alternative to improve community nutritional intake. In addition, TOGA can contribute to increasing family income, improving the health of the residential environment, and preserving medicinal plants and national cultural heritage. The role of the family in the community is important in supporting efforts to fulfill the nutritional needs of postpartum mothers. This activity is useful for meeting family food needs. We invite the community of Kandangjati Kulon Village to utilize their home yards by planting various plants, including TOGA or medicinal plants. This initiative aims to increase the availability, access, and utilization of food for families, especially medicinal plants grown in each household. The materials delivered include methods for utilizing and processing TOGA plants. The implementation stage involves distributing attendance lists prepared by the community partnership program team to participants, providing explanations of the activity process, and promoting the cultivation of TOGA as an effort to fulfill the nutritional needs of postpartum mothers.